Biological effects of sub-lethal doses of glyphosate and AMPA on cardiac myoblasts - Arrigo, Elisa; Gilardi, Sara; Muratori, Luisa; Raimondo, Stefania; Mancardi, Daniele (Frontiers in Physiology, 2023)
Glyphosate is the active compound of different non-selective herbicides, being the most used agriculture pesticide worldwide. Glyphosate and AMPA (one of its main metabolites) are common pollutants of water, soil, and food sources such as crops. They can be detected in biological samples from both exposed workers and general population. Despite glyphosate acts as inhibitor of the shikimate pathway, present only in plants and some microorganisms, its safety in mammals is still debated. Acute glyphosate intoxications are correlated to cardiovascular/neuronal damages, but little is known about the effects of the chronic exposure. Our study aims to evaluate the direct biological effects of different concentrations of pure glyphosate or AMPA on a rat-derived cell line of cardiomyoblasts (H9c2) in acute (1 – 2 hours) or sub-chronic (24 – 48 hours) settings. We show that acute exposure to high doses (above 10 mM) of glyphosate and AMPA triggers immediate cytotoxic effects: reduction in cell viability, increased ROS production, morphological alterations and mitochondrial dysfunction. When exposed to lower glyphosate concentrations (1 µM – 1 mM), H9c2 cells showed only a slight variation in cell viability and ROS production, while mitochondrial dynamic was unvaried. Moreover, the phenotype was completely restored after 48 hours of treatment. Surprisingly, the sub-chronic (48 hours) treatment with low concentrations (1 µM – 1 mM) of AMPA led to a late cytotoxic response, reflected in a reduction in H9c2 viability. The clear comprehension of the extent of human exposure to these molecules remains pivotal to have a better critical view of the available data.